The dynamic of opsono-phagocytic reactions of cows as a result of applying of ecologically clean bio solute «Poltavsky bishofit» - Киричко, Б. П.; Скрипка, М. В.; Киричко, О. Б. (Scientific Progress & Innovations, 2012)
This article is based on the researchers’ results of the dynamic of opsono-phagosytic reactions of the healthy and Subclinical Mastitis sick cows with external application of ecologically clean solute «Poltavsky bishofit» at different terms of use. Bishofit is the biological mixture of salts from the dried old Perm Sea. Opsono-phagosytic reaction is extremely important for the organizm resistance. The research found out the increase of neutrophils’ phagocytic activity, the increase of Phagocytic index and Phagocyte number. The most effective, due to the data of opsonophagocytic reaction, was application of the solution «Poltavsky bishofit» within the intervals of 12 and 24hours.